PENGARUH PEMANFAATAN TEPUNG ECENG GONDOK (EICHHORNIA CRASSIPES) FERMENTASI DALAM RANSUM TERHADAP BOBOT POTONG, BOBOT KARKAS DAN PERSENTASE KARKAS ITIK LOKAL JANTAN PADA UMUR SEMBILAN MINGGU - Irwan Lase; Untung Pardosi (JASA PADI, 2020)
ABSTRACTThis research aims to determine the effect of giving fermented watersheds (Eichhornia crassipes)flour in feed on the cut weight, carcass weight and carcas percentage of male local ducks age of 9 weeks.This research was carried out at Porlak Nommensen, Simalingkar B, Medan Tuntungan during 9 weeks.Began on March to May 2019. This use 40 male local ducks. The research method was used theexperimental method using a completely randomized design (CRD) consisted of 5 treatments and 4replications, that are P0 (basal ration), P1 (5% fermented water hyacinth flour in basal ration), P2 (10%fermented water hyacinth flour in basal ration), P3 (15% fermented water hyacinth flour in basal ration)and P4 (20% fermented water hyacinth flour in basal ration). The data obtained in this research thenanalyzed with analysis of variance (ANOVA) then continued with the Least Significance Different (LSD)at the level 5%. Conclusion by the result of research showed that the giving of fermented water hyacinth(Eichhornia crassipes) flour in feed of male local ducks age of9 weeks gives a significant influence on cutweight, carcass weight and carcass percentage. The best giving of fermented water hyacinth flour foundon P3 with giving level 15%.Key words : Watersheds, Fermentation, Male local duck, Cut weight, Carcass weight and percentage.